Genetically modified organisms in food : production, safety, regulation and public health - Watson, Ronald R.; Preedy, Victor R. (Elsevier Science, 2016)
Genetically Modified Organisms in Food focuses on scientific evaluation of published research relating to GMO food products to assert their safety as well as potential health risks. This book is a solid reference for researchers and professionals needing information on the safety of GMO and non-GMO food production, the economic benefits of both GMO and non-GMO foods, and includes in-depth coverage of the surrounding issues of genetic engineering in foods. This is a timely publication written by a team of scientific experts in the field who present research results to help further more evidenc.